Fresh sweet cherry fruit characterization and differentiation by Raman spectroscopy coupled with PCA - Volić Mina; Obradović Nataša; Milošević Nebojša; Pećinar Ilinka (Acta Agriculturae Serbica)
This study has shown that Raman spectroscopy can be used to analyze the unique patterns of sweet cherry cultivars ('G-2', 'Burlat', 'Canetova', 'Ohridska Crna', and 'Dolga Šiška'). As the minor scattering effect of water molecules guarantees no water interference, Raman spectroscopy can be applied to unprocessed, fresh fruits compared to other methods. The obtained Raman spectra indicate that using the above method can effectively confirm the authenticity of different cherry varieties. By combining Raman spectroscopy with principal component analysis (PCA), samples nutritionally similar to studied cherry cultivars can be distinguished.